Training in pediatric hepatology across Europe: a survey of the National Societies Network (2016-2019) of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition - Papadopoulou, Alexandra; Ribes-Koninckx, Carmen; Noni, Maria; Koutri, Eleni; Karagianni, Maria-Vasiliki; Protheroe, Sue; Guarino, Alfredo; Mas, Emmanuel; Wilschanski, Michael; Roman, Enriqueta; Escher, Johanna; Furlano, Raoul I; et al. (Annals of gastroenterology, 2022)
BACKGROUND: The widely recognized burden of liver diseases makes training in pediatric hepatology (PH) imperative. The aim of this survey, which was part of a global survey on training in pediatric gastroenterology, hepatology and nutrition (PGHN) across Europe, was to assess the PH and liver transplantation (LT) infrastructure, staff and training programs in PGHN training centers. METHOD: Standardized questionnaires were collected from training centers via the presidents/representatives of the National Societies Network of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) from June 2016 to December 2019. RESULTS: A total of 100 PGHN training centers participated in the survey (14/100 were national referral centers in PH and/or LT). Dedicated PH clinics were available in 75%, but LT clinics in only 11%. Dedicated beds for PGHN inpatients were available in 47/95 (49%) centers. Full-time or part-time specialists for PH care were available in 31/45 (69%) and 11/36 (31%) centers, respectively. Liver biopsies (LB) were performed in 93% of centers by: a PGHN specialist (35%); an interventional radiologist (26%); a pediatric surgeon (4%); or a combination of them (35%). Dividing the annual number of LBs in the centers performing LBs by the number of trainees gave a median (range) of 10 (1-125) per trainee. Transient elastography was available in 60/92 (65%) of centers. CONCLUSIONS: The survey highlighted the differences and shortcomings in PH training across Europe. ESPGHAN should take initiatives together with National Societies to ensure the acquisition of PH knowledge and skills according to the ESPGHAN curriculum.An infographic is available for this article at: http://www.annalsgastro.gr/files/journals/1/earlyview/2022/Infographic-Hepatology-training-paper.pdf.
Keywords: nutrition; children; Hepatology; pediatric gastroenterology; training